Os liberais e o espectro político unidimensional : direita, esquerda ou algo mais? - Ostermann, Fábio Maia (2014)
This research has the objective of analyzing the current validity of the political-ideological dichotomy Right-Left approaching specifically the case of Liberalism and by questioning its position on the political spectrum. A historical panorama of this dichotomy is presented, since its emergence until contemporary times, coming to a brief debate about the current validity of the one-dimension political-ideological spectrum. Following, Liberalism is discussed as political philosophy and through its positions as such since its doctrinaire origins– with special attention to the development of liberal ideas in Brazil until today. After that, there will be an analysis of qualitative interviews made with eight leaders from seven of the most important institutions in so called ―liberal movement‖ in Brazil. The interviews aim at better understanding how these actors – selected among founders and directing figures at the most highlighted organizations focused on defending liberal ideas in Brazil – see the positioning of their own organizations and that of Liberalism regarding the one-dimension scale Left-Right. These interviews will allow a reflection on the perception of liberals about the suitability of this dichotomy, alternatives and the relation of liberals with politics.